Dynamics of the Neo-MABIMS Criteria in Determining the Beginning of the Hijri Month in Indonesia (1443–1446 H) - Wahyuningsih, Yuniar; Firdiansyah, Ahmad Roihan (Al-Hilal: Journal of Islamic Astronomy, 2025)
This study explores the ongoing variations in determining the beginning of the Hijri month in Indonesia, despite the official adoption of the Neo-MABIMS criteria by the Ministry of Religious Affairs of the Republic of Indonesia. Employing a descriptive qualitative approach, the research outlines and deductively analyzes data related to formulating and implementing these criteria. The findings reveal two key points: first, discrepancies persist in determining the beginning of the Hijri month. Since implementing the Neo-MABIMS criteria up to Jumada al-Awwal 1446 H, two months, Jumada al-Akhirah 1445 H, and Muharram 1446 H, have produced different outcomes. Second, even when identical criteria are applied, differences in methodological approaches may lead to either divergent or convergent results. This study recommends future research involving expert interviews to strengthen analytical depth and include updated observational data on Hijri month determination to enhance the comprehensiveness and accuracy of the findings.